EFFECT OF ORGANIZATIONAL COMMITMENT AND COMPENSATION ON WORK DISCIPLINE AND IMPACT ON PERFORMANCE EMPLOYEES - Anista Yulia Ratnawati; Suci Purwandari (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
This research was conducted at the Vocational Campus and aims to determine the effect of work discipline on employee performance which has decreased due to many disciplinary violations. In addition, to find out how promotion and compensation affect employee performance improvement. Research data obtained through questionnaires and interviews. The sample used in the study was 51 respondents. The data obtained were processed using descriptive analysis and quantitative statistical analysis. Quantitative analysis uses multiple regression analysis to determine the effect of the independent variable on the dependent variable, but before the test is carried out, the validity and reliability tests are carried out first and the requirements test. The results of the multiple regression analysis test showed a significant F value, with a correlation value of determination adjusted R2 of 0.457. This shows that work discipline, promotion and compensation significantly affect employee performance together with a close relationship of 45.7%. This shows that to improve employee performance, it is necessary to increase work discipline, provide opportunities for promotion and provide compensation according to employee expectations.